pdf Strategies for Inclusive FinTech Adoption in Rural Communities: A Systematic Literature Review - Fatmasari, Raden Roro (Yayasan Kreatif Indonesia Emas, 2024)
This paper presents a systematic literature review to identify and synthesize effective strategies for enhancing fintech adoption in rural and underserved communities. Drawing on a comprehensive body of research from peer-reviewed journals, development agencies, and global case studies published between 2012 and 2024, the study meticulously examines key adoption barriers, essential enabling technologies, critical sociocultural dynamics, and the policy frameworks that collectively support inclusive fintech ecosystems in remote and marginalized settings. Through a critical thematic analysis, this work provides profound insights into how fintech initiatives can be strategically tailored for meaningful rural impact. The paper culminates in a set of actionable recommendations for multi-stakeholder collaboration, emphasizing that a holistic, context-specific approach is vital for bridging the financial inclusion gap.